Balinese Phonology Ungasan Dialect Generative Phonology Study - sutresna, I Made Agus Atseriyawan Hadi; Putra, Anak Agung Putu; Suryati, Ni Made (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2023)
The Balinese Ungasan dialect (BBDU) has a uniqueness if compared to standard Balinese (BBB), on the other side, it has some similarities with the Balinese dialect of Bali Aga (DBA). This research will focus on the phonological level post-lexical phonological processes, and BBDU phonological rules. The theory used was generative phonological theory. Observational and proficient methods were used in data collection, the distributional and identity methods were used to analyze the data and formal and informal methods were used in presenting data analysis.The five post-lexical phonological rules are divided into two parts. Phonological rules caused by clitics in BBDU: 1) Addition of consonant [n] PR; 2) Addition of consonants [n] PR; and 3) Vocal Drop /u/ PR. The phonological rules for question words in BBDU, 4) Addition of vowels PR; and 5) Addition of consonant [h].